Skin pretreatment with microneedles prior to pilocarpine iontophoresis increases sweat production. (13th May 2013) - Wing, David; Prausnitz, Mark R.; Buono, Michael J.
Summary Collection of sweat via pilocarpine iontophoresis is commonly used to diagnose cystic fibrosis (CF), with thousands of tests performed each day. The main source of resistance to the passage of pilocarpine ions to the sweat glands is the electrical resistance of the stratum corneum. It was hypothesized that pretreating the skin with 0·5 mm‐long microneedles would significantly decrease this resistance, thus increasing pilocarpine's permeation into the skin. Improved permeation should result in significantly reduced time to sweat initiation, time to collection of a clinically meaningful amount of sweat, and increased total amount of sweat produced in 15 min. Subjects (n = 12) had two 5 cm2 areas on the forearm measured, marked and randomized to experimental (microneedles + iontophoresis) or control (iontophoresis alone). Microneedle pretreatment was conducted using a 35‐needle microneedle stamp in a manner that 20 applications completely covered the 5 cm2 treatment area. This was repeated five times for a total of 100 applications. Both experimental and control sites were placed under iontophoresis (1·5 mA) for 5 min. Microneedle pretreatment significantly decreased mean skin resistance (260 ± 27 kΩ versus 160 ± 19 kΩ, P = 0·006), while significantly increasing mean sweat rate (0·76 ± 0·35 versus 0·54 ± 0·19 μl cm2 min−1, P = 0·007). No significant difference was found concerning pain (P = 0·059), number of active sweat glands (P = 0·627) or the osmolality of the collected sweat (P = 0·636). The results of this study suggest that microneedle pretreatment prior to pilocarpine iontophoresis significantly increases sweat production. Such results have the potential to improve the methodology currently used to diagnose cystic fibrosis and, more broadly, to administer drugs via the skin.